Vascular regression precedes motor neuron loss in the FUS (1-359) ALS mouse model - Martin Crivello; Marion C. Hogg; Elisabeth Jirström; Luise Halang; Ina Woods; Megan Rayner; Karen S. Coughlan; Sebastian A. Lewandowski; Jochen H. M. Prehn (The Company of Biologists, 2019)
Amyotrophic lateral sclerosis (ALS) presents a poorly understood pathogenesis. Evidence from patients and mutant SOD1 mouse models suggests vascular damage may precede or aggravate motor dysfunction in ALS. We have previously shown angiogenin (ANG) treatment enhances motor neuron survival, delays motor dysfunction and prevents vascular regression in the SOD1G93A ALS model. However, the existence of vascular defects at different stages of disease progression remains to be established in other ALS models. Here, we assessed vascular integrity in vivo throughout different disease stages, and investigated whether ANG treatment reverses vascular regression and prolongs motor neuron survival in the FUS (1-359) mouse model of ALS. Lumbar spinal cord tissue was collected from FUS (1-359) and non-transgenic control mice at postnatal day (P)50, P90 and P120. We found a significant decrease in vascular network density in lumbar spinal cords from FUS (1-359) mice by day 90, at which point motor neuron numbers were unaffected. ANG treatment did not affect survival or counter vascular regression. Endogenous Ang1 and Vegf expression were unchanged at P50 and P90; however, we found a significant decrease in miRNA 126 at P50, indicating vascular integrity in FUS mice may be compromised via an alternative pathway. Our study demonstrates that vascular regression occurs before motor neuron degeneration in FUS (1-359) mice, and highlights that heterogeneity in responses to novel ALS therapeutics can already be detected in preclinical mouse models of ALS. This article has an associated First Person interview with the joint first authors of the paper.